RECONSTRUCTING SJAFRUDDIN PRAWIRANEGARA'S ISLAMIC ECONOMIC STRATEGY IN ADDRESSING MODERN ECONOMIC CHALLENGES - Affandi, Faisal; Hamonangan (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study explores the reconstruction of Sjafruddin Prawiranegara’s Islamic economic strategies in addressing modern economic challenges. Sjafruddin, a prominent figure in Indonesia’s economic history, emphasized the principles of social justice, economic independence, and sustainable resource management, which align with the foundations of Islamic economics. This research employs a qualitative approach through an in-depth literature review, analyzing various sources, including books, scholarly articles, and official documents related to Sjafruddin’s economic thought. The findings indicate that Sjafruddin’s strategies remain relevant in contemporary economic contexts, particularly in fostering equitable wealth distribution, minimizing economic disparities, and promoting national self-sufficiency. His ideas advocate for an economic framework that not only focuses on growth but also ensures ethical, just, and sustainable economic development. Additionally, this research highlights the policy implications of his thought, suggesting that modern economies, particularly in developing countries, can benefit from integrating Islamic economic principles into their financial and economic systems. By revisiting and reconstructing Sjafruddin Prawiranegara’s economic strategies, this study contributes to the discourse on Islamic economic development and offers a viable alternative to conventional economic models. The research underscores the importance of an economic system that balances efficiency with ethical considerations, ensuring long-term sustainability and economic resilience.